Cervical Necrotizing Fasciitis Caused by Dental Extraction - José Alcides Arruda; Eugênia Figueiredo; Pâmella Álvares; Luciano Silva; Leorik Silva; Antônio Caubi; Marcia Silveira; Ana Paula Sobral (Hindawi Limited, 2016)
Cervical necrotizing fasciitis is an unusual infection characterized by necrosis of the subcutaneous tissue and fascial layers. Risk factors for the development of necrotizing fasciitis include diabetes mellitus, chronic renal disease, peripheral vascular disease, malnutrition, advanced age, obesity, alcohol abuse, intravenous drug use, surgery, and ischemic ulcers. This report presents a case of necrotizing fasciitis in the cervical area caused by dental extraction in a 73-year-old woman. Cervical necrotizing fasciitis in geriatric patient is rare, and even when establishing the diagnosis and having it timely treated, the patient can suffer irreversible damage or even death. Clinical manifestations in the head and neck usually have an acute onset characterized by severe pain, swelling, redness, erythema, presence of necrotic tissue, and in severe cases obstruction of the upper airways. Therefore, the presentation of this clinical case can serve as guidance to dentists as a precaution to maintain an aseptic chain and be aware of the clinical condition of older patients and the systemic conditions that may increase the risk of infections.